2018
DOI: 10.7150/ijms.24715
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TLR4 in silica-induced inflammation: An underlying mechanism of silicosis

Abstract: Silicosis is an incurable lung disease affecting millions of workers in hazardous occupations. It is caused by chronic exposure to the dust that contains free crystalline silica. Silica-induced lung damage occurs by several main mechanisms including cell death by apoptosis, fibrosis and production of cytokines. However, the signal pathways involved in these mechanisms are not fully characterized. In this study, the toll-like receptor 4 (TLR4)-related signal pathway was examined in silica-treated U937-different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Which immune reactions that will ultimately be triggered depend on both local conditions for immune activation and on genetic constitution, mainly in MHC genes expressed by the host. Of interest in the context of local immune activation is that smoke (containing char and other agents) as well as silica dust can activate dendritic cells as well as monocytes/macrophages as antigen-presenting cells by effects mediated via pattern recognition molecules, including TLR4 [167][168][169]. That such events happen also in vivo in patients is indicated from the demonstration of germinal centre-like structures in the lungs of ACPA-positive newly diagnosed RA patients [163,170].…”
Section: Gene-environment Interactionsmentioning
confidence: 99%
“…Which immune reactions that will ultimately be triggered depend on both local conditions for immune activation and on genetic constitution, mainly in MHC genes expressed by the host. Of interest in the context of local immune activation is that smoke (containing char and other agents) as well as silica dust can activate dendritic cells as well as monocytes/macrophages as antigen-presenting cells by effects mediated via pattern recognition molecules, including TLR4 [167][168][169]. That such events happen also in vivo in patients is indicated from the demonstration of germinal centre-like structures in the lungs of ACPA-positive newly diagnosed RA patients [163,170].…”
Section: Gene-environment Interactionsmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are highly conserved evolutionary receptors of the innate immunity, which constitute the first barrier against pathogens 49 - 51 . In our study we found significantly lower expression of not only TLR5 , which confirms previous studies, but also TLR1, 2, 4, 6, 8 and TLR10 were downregulated in our preterm group, when compared with term babies.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity and biodiversity of agriculture dust exposures is increasingly recognized, and animal and human studies have defined roles for TLR2/TLR4/TLR9signaling pathways [8][9][10][11][12]. The TLR/IL-1R/IL-18R adaptor protein myeloid differentiation factor 88 (MyD88) that is used by all TLRs except for TLR3 [13] has been shown to have a fundamental role in the acute inflammatory response to organic dust [10,14,15] as well as other inflammatory exposures [16,17]. MyD88 signaling mediates bleomycin-induced IL-17B expression in alveolar macrophages to promote pulmonary fibrosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…MyD88 signaling mediates bleomycin-induced IL-17B expression in alveolar macrophages to promote pulmonary fibrosis [16]. In silica-induced fibrosis, silica dust increases MyD88 expression in macrophages [17]. In experimental asthma, MyD88 expression in epithelial cells mediates eosinophilia whereas MyD88 expression in conventional dendritic cells controls the neutrophilic response [18].…”
Section: Introductionmentioning
confidence: 99%